Pengaruh Participation Budgeting, Information Asimetry dan Job Relevant Information terhadap Budget Slack pada Institusi Pendidikan (Studi pada Institusi Pendidikan Universitas Kristen Maranatha) - Christine Dwi K. S.; Lidya Agustina (Universitas Kristen Maranatha, 2010)
The purpose of this research is to analyze and examine the hyphothesis effect of participation budgeting on job relevant information and information asimetry as a moderating variable , and effect of participation budgeting and information asimetry on budget slack and job relevant information as mediating varible. The respondent of this research are 30 structural staf of program and ministry in Maranatha Christian University who have participated to make budgeting. This method that is used in this research is causal. Sampling technique employed in this research is purposive random sampling. It is using simple regression analysis to examine the effect participation budgeting on job relevant information and asimetry information as a moderated variable, and effect of participation budgeting and information asimetry on budget slack and job relevant information as a variabel mediating. This result of this research shows that participation budgeting give positive effect to job relevant information and information asimetry as moderating variable, and participation budgeting and information asimetry have negative effect to budget slack and job relevant information as a mediating variable. Increasing on the participation budgeting and information asimetry and job relevant information, will effect decreasing on budget slack. Keywords: participation budgeting, information asimetry, job relevant information, budget slack